2000
DOI: 10.1089/vim.2000.13.511
|View full text |Cite
|
Sign up to set email alerts
|

Cytolytic Function for Pseudorabies Virus-Stimulated Porcine CD4+CD8dull+Lymphocytes

Abstract: We previously observed that pseudorabies (PRV) virus-specific killing in vitro was mediated by CD6+ CD8+ lymphocytes. Also a high percentage of CD4+ lymphocytes, among these CD6+ CD8+ lymphocytes, was observed. The purpose of this study was, therefore, to further characterize the killing ability of PRV-stimulated CD4+ CD8+ lymphocytes. Peripheral blood mononuclear cells (PBMC) were isolated from blood of PRV-immune pigs and were stimulated in vitro with PRV. After 6 days, the frequency of CD4+ CD8+ lymphocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…Consistent with that, an increased frequency of activated CD4 ϩ T cells associated with enhanced generation of the SwIV-specific mucosal IgA and an increased frequency of activated CD8 ϩ T cells in pig lungs were detected. Activated CD4 ϩ CD8 ϩ T cells in pigs possess T-helper, cytolytic, and memory properties, important for the viral clearance (12). Interestingly, in SwIV-infected BAL fluid, TBLN, and tonsils, significantly higher frequencies of CD4 ϩ CD8 ϩ T cells were detected.…”
Section: Discussionmentioning
confidence: 97%
“…Consistent with that, an increased frequency of activated CD4 ϩ T cells associated with enhanced generation of the SwIV-specific mucosal IgA and an increased frequency of activated CD8 ϩ T cells in pig lungs were detected. Activated CD4 ϩ CD8 ϩ T cells in pigs possess T-helper, cytolytic, and memory properties, important for the viral clearance (12). Interestingly, in SwIV-infected BAL fluid, TBLN, and tonsils, significantly higher frequencies of CD4 ϩ CD8 ϩ T cells were detected.…”
Section: Discussionmentioning
confidence: 97%
“…The porcine CD4 + CD8 + population contains memory T helper cells that recognize antigens in an MHC class II-restricted manner [33]. The CD4 + CD8 + are multifunctional, as they express perforin and mediate antigen-specific cytolytic activity against virus-infected target cells [34,35]. It is not clear why the CD4 + CD8 + CD25 EI responses of animals vaccinated with NS1 126 TX98 remained low prior to challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Summerfield et al [23] demonstrated that CD4+CD8+ cells can function as memory T-helper cells which proliferate upon stimulation with recall antigen. The CD4+CD8+ T cells were found to be associated with protection in pigs vaccinated against PRV [24]. The study of the cellular immune response to virus or vaccines in the natural host is of the utmost importance for understanding the interaction between the pathogen and the swine immune system [25].…”
Section: Introductionmentioning
confidence: 99%